Flexibility of frequent clause openers in talk-in-interaction: Det ‘it, that’ and så ‘then’ in the prefield in Danish - Puggaard, Rasmus (Nordic journal of linguistics, 2019)
Through in-depth analysis of the use of det ‘it, that’ and så ‘then’ occupying the first clausal position (the prefield) in Danish talk-in-interaction, this paper investigates how speakers use highly flexible linguistic elements to their advantage when commencing clauses in real time. These particular words are useful when occupying the prefield, because their flexible nature means that they can be used even when speakers do not have a full format ready for the carrier clause, as long as they have some idea of the interactional purpose of the clause and its information structural prerequisites. The dominating frequency of the most frequent clause openers goes largely unmentioned in previous accounts of the prefield, and the use of det ‘it, that’ and så ‘then’ challenges the popular notion that the textually unmarked prefield is also the grammatical subject of the carrier clause.